Effects of arsenic exposure on the PI3K/Akt/NF-κB signaling pathway in the hippocampus of offspring mice at different developmental stages - Yingying Qi; Jiaqi Sun; Huan Wang; Haiyang Yu; Xiaoxia Jin; Xu Feng; Yan Wang (Ecotoxicology and Environmental Safety, 2024)
The primary purpose of present study was to explore the effects of arsenic exposure on the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt)/nuclear transcription factor-κB (NF-κB) signaling pathway in the hippocampus of offspring mice at different developmental stages. Sodium arsenite (NaAsO2) at doses of 0, 15, 30 or 60 mg/L administered to female mice and their pups. The nuclear translocation levels of NF-κB were assessed by EMSA. Real-time RT-PCR was used to measure Akt, NF-κB and PI3K mRNA levels. Protein expressions of PI3K, p-Akt, inhibitor kappa B kinase (IKK), p-NF-κB, protein kinase A (PKA), inhibitor kappa B (IκB), and cAMP response element-binding protein (CREB) were measured by Western blot. Results disclosed that exposure to 60 mg/L NaAsO2 could suppress NF-κB levels of nuclear translocation of postnatal day (PND) 20 and PND 40 mice. Arsenic downregulated the transcriptional and translational levels of PI3K, Akt and NF-κB. Additionally, protein expressions of p-IKK, p-IκB, PKA and p-CREB also reduced. Taken together, results of present study indicated that arsenic could downregulate the PI3K/Akt/NF-κB signaling pathway, particularly on PND 40, which might be involved in the cognitive impairments.